Construction of a nomograph model of impact of patency time after percutaneous balloon dilation for arteriovenous fistula stenosis - Shu Chang -dong; Mei Ji-ben; Chen Zhong-hui; Gui Dong-dong (Linchuang shenzangbing zazhi)
ObjectiveTo explore the influencing factors of patency time after percutaneous transluminal angioplasty （PTA） for arteriovenous fistula （AVF） stenosis and construct a nomograph prediction model.MethodsFrom February 2019 to May 2022， 125 patients receiving vascular ultrasonic evaluations and undergoing PTA for AVF stenosis were selected as study subjects and included into training set. According to the same criteria， from June to December 2022， another 42 patients （n=42） receiving vascular ultrasound included into validation set for verifying the effectiveness of the prediction model. Multivariate Cox analysis was utilized for identifying the risk factors affecting primary patency time of internal fistula post-PTA. Stepwise regression was employed for further screening important factors and constructing and validating a nomogram prediction model.ResultsPrimary patency rate was 96.0% at Month 3， 85.6% at Month 6 and 64.0% at Month 12 post-PTA. Multivariate Cox analysis results indicated that diabetes mellitus（OR=1.714，95%CI：1.034~2.308）， AVF establishment time（OR=4.190，95%CI：1.684~8.807）， stenotic length（OR=2.008，95%CI：1.066~3.050）， maximal balloon pressure （OR=2.342，95%CI：1.107~4.078）and blood magnesium（OR=0.722，95%CI：0.620~0.823） were independent influencing factors for short patency time of internal fistula post-PTA （P<0.05）. Stepwise regression analysis identified that time of AVF establishment， stenotic length， maximal balloon pressure and blood magnesium were most closely correlated with the first stage patency time of postoperative internal fistula. The evaluation results of the model hinted at a decent discrimination， a high accuracy and great effectiveness. Patients were assigned into three risk groups based on an optimal threshold， namely <112 points （low risk），≥112 points and <152 points （medium risk） and ≥152 points （high risk）.ConclusionTime of AVF establishment， length of stenosis， maximal balloon pressure and blood magnesium are all most correlated with the first stage patency time of postoperative internal fistula. The nomogram prediction model based on risk factors has some clinical value.